The impact of COVID-19 on emotional exhaustion: depersonalization and self-perceived low performance among hospital pharmacists in Brazil - Helena Marcia MORAES; Maria Rita NOVAES; Christian Oscar MOSCA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: To analyze the impact of the covid-19 pandemic on the dimensions of burnout Syndrome - emotional exhaustion (EE), depersonalization (DP), and reduced professional accomplishment (RP) - among hospital pharmacists (HP) in Brazil. The research compares data from 2011 and 2022, exploring the association between social organization profile and working environment with these burnout dimensions. Method: Conducted in analytical cross-sectional format, the study selected HP associated with the Brazilian Society of Hospital Pharmacy. Data were collected through a questionnaire, addressing socio-organizational profiles, as well as the Maslach burnout Scale. Statistical analyses, including frequency, chi-square test, and Cronbach's alpha validation, were employed to examine associations between variables and burnout dimensions. Results: A total of 174 HP participated in 2011, and 237 in 2022. Both periods revealed links between "job satisfaction" and "compensation" with the dimensions EE, DP, and RP, before and after the pandemic. The 2022 study also highlighted the lack of training encouragement as associated with burnout dimensions. Working hours maintained associations in both studies, except RP in the most recent research. Variables such as contract type and work environment profile did not show significant relationships. Education did not correlate with dimensions in the most recent study, whereas the number of children was associated with DP in 2022, compared to associations with EE and DP in the previous study. Marital status and gender showed a connection with RP in both studies, whereas age related to DP in the 2011 study and only with DP in the most recent study. The prevalence of burnout among HP increased after the pandemic, with 68.8% exhibiting the syndrome in 2022, compared to 44.0% in 2011. Conclusion: There was an impact of the covid-19 pandemic on the health of hospital pharmacists. The relationship between job satisfaction, compensation, and working hours with burnout dimensions highly highlight the need for policies and organizational practices to focus on the well-being of these professionals. The significant increase in burnout prevalence after the pandemic highlights the importance of strategies to support the mental and occupational HP health, requiring discussions and actions both within healthcare institutions and in governmental and professional realms.